Proceedings of the ACM Symposium on Virtual Reality Software and Technology 2003
DOI: 10.1145/1008653.1008691
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention based information culling for Distributed Virtual Environments

Abstract: The central goal in Distributed Virtual Environments (DVEs) is to provide an experience of the shared world that is perceptually plausible for the immersed user. This has to be achieved in the face of network issues such as bandwidth limitations and latencies which make total synchronism impossible. Techniques have been devised to help; some optimise network use by limiting what is transmitted, others try to disguise the effects of network 'glitches' at the user's client machine -for example smoothing policies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…A psychologically oriented approach for visibility-based interest management was proposed in Beeharee et al [2003]. This approach is based on a number of visual attention models that exploit the fact that only feature information (e.g., colour, orientation, and participant activity) can catch the attention of a human.…”
Section: Psychologically Oriented Approachesmentioning
confidence: 99%
“…A psychologically oriented approach for visibility-based interest management was proposed in Beeharee et al [2003]. This approach is based on a number of visual attention models that exploit the fact that only feature information (e.g., colour, orientation, and participant activity) can catch the attention of a human.…”
Section: Psychologically Oriented Approachesmentioning
confidence: 99%
“…Thus, we suggested that they should be made to look more interactive to draw user attention to them. Visual attention process has been studied extensively within cognitive science, neurology and psychology, but also within VEs especially on taskoriented VEs, such as interactive 3D games (Beeharee et al, 2003), (Bernhard et al, 2010), (El-Nasr & Yan, 2006). To enhance interactivity of 3D elements, Beeharee et al (2003) suggest that highly contrasting colour and object orientation changes compared to their neighbours are most likely to gain visual attention from the user.…”
Section: Embedded Interactive 3d Elements and Objectsmentioning
confidence: 99%
“…1 The encoder was configured to generate streams in the scalable high profile with one base layer and one coarse-grained scalable or MGS enhancement layer, a GOP size of 4 frames with hierarchical B-frames, an intra period of 12 frames, inter-layer prediction and CABAC encoding. Note that SVC defines the set of pictures anchored by two successive key pictures together with the first key picture as a group of picture, where key pictures are usually encoded as P-frames within an intra period, see [13].…”
Section: Subjective Quality Evaluationmentioning
confidence: 99%
“…Visual acuity in human's foveal field-of-vision decreases from the center towards the outside while sensitivity to motion effects increases [1,9,12]. On mobile screens, the complete screen is in the central high acuity region and therefore detail is resolved throughout the displayed image at almost the same fidelity.…”
Section: Small Versus Large Screensmentioning
confidence: 99%